The crowdfunding for projects social: financial instrument a social cohesion element and wellness generator - Sajardo Moreno, Antonia; Pérez Sempere, Salvador (Cooperativismo & Desarrollo, 2020)
The objective of this article is to deepen the study of crowdfunding and the role it performs in the field of social entities and projects, from a triple perspective. First, valuing its role as a fundraising instrument that generates financial independence and advances in its political-social autonomy. Second, as a cohesive element of society and expansion of participatory democracy. Third, in achieving social welfare improvements —Upper Pareto movements—. The work methodology has been the Big Data analysis of the representative platforms of social crowdfunding in the Spanish State, migranodearena.org and goteo.org, in the donation and reward modality respectively, from its creation date until December 2016.